Influence of cell surface hydrophobicity on attachment of Campylobacter to abiotic surfaces - Nguyen, V.; Turner, M.; Dykes, Gary (2011)
This work aimed to investigate the influence of physicochemical properties and prior mode of growth (planktonic or sessile culture) on attachment of 13 Campylobacter jejuni strains and 5 Campylobacter coli strains isolated from chicken samples to three abiotic surfaces: stainless steel, glass and polyurethane. Water contact angle and zeta potential measurements indicated that the strains varied with respect to surface hydrophobicity (17.6 ± 1.5 to 53.0 ± 2.3°) and surface charge (−3.3 ± 0.4 to −15.1 ± 0.5 mV). Individual strains had different attachment abilities to stainless steel and glass (3.79 ± 0.16 to 5.45 ± 0.08 log cell cm−2) but did not attach to polyurethane, with one exception. Attachment of Campylobacter to abiotic surfaces significantly correlated with cell surface hydrophobicity (P ≤ 0.007), but not with surface charge (P ≥ 0.507). Cells grown as planktonic and sessile culture generally differed significantly from each other with respect to hydrophobicity and attachment (P < 0.05), but not with respect to surface charge (P > 0.05). Principal component analysis (PCA) clustered strains into three groups (planktonic culture) and two groups (sessile culture) representing those with similar hydrophobicity and attachment. Of the four highly hydrophobic and adherent strains, three were C. coli suggesting that isolates with greater hydrophobicity and adherence may occur more frequently among C. coli than C. jejuni strains although this requires further investigation using a larger number of strains. Assignment of pulsed-field gel electrophoresis profiles to PCA groups using Jackknife analysis revealed no overall relationship between bacterial genotypes and bacterial attachment. No relationship between serotype distribution and bacterial attachment was apparent in this study.